Design and implementation of a scalable correlator based on ROACH2 + GPU cluster for tianlai 96-dual-polarization antenna array - Wang, Zhao; Li, Ji-Xia; Zhang, Ke; Wu, Feng-Quan; Tian, Hai-Jun; Niu, Chen-Hui; Zhang, Ju-Yong; Chen, Zhi-Ping; Yu, Dong-Jin; Chen, Xue-Lei (Frontiers in Astronomy and Space Sciences, 2024)
The digital correlator is one of the most crucial data processing components of a radio telescope array. With the scale of radio interferometeric array growing, many efforts have been devoted to developing a cost-effective and scalable correlator in the field of radio astronomy. In this paper, a 192-input digital correlator with six CASPER ROACH2 boards and seven GPU servers has been deployed as the digital signal processing system for Tianlai cylinder pathfinder located in Hongliuxia observatory. The correlator consists of 192 input signals (96 dual-polarization), 125-MHz bandwidth, and full-Stokes output. The correlator inherits the advantages of the CASPER system, for example, low cost, high performance, modular scalability, and a heterogeneous computing architecture. With a rapidly deployable ROACH2 digital sampling system, a commercially expandable 10 Gigabit switching network system, and a flexible upgradable GPU computing system, the correlator forms a low-cost and easily-upgradable system, poised to support scalable large-scale interferometeric array in the future.